Factors affecting mobility of harmonic symbols - Osman, Osman Abdalla Adam (Edelweiss Applied Science and Technology, 2024)
In this paper, we have illustrated the Bergmann domains and the Toeplitz operators with their symbiotic symbols in some special domains in order to clarify the properties that correspond to the fixed values. And we characterize the bounded harmonic functions for which the Toeplitz operators Bergman space are essentially commuting.